GAYA KEPEMIMPINAN DAN PRAKTEK BISNIS SERTA PENGARUHNYA TERHADAP KINERJA UKM DI PROPINSI ACEH - Jullimursyida Jullimursyida (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2018)
This study was conducted to determine the effect of leadership style and business practices that run on the performance of small and medium enterprises. The data for this study will be obtained by distributing questionnaires. The questionnaire had been developed distributed to employees of SMEs. In order to achieve the research objectives and addressing existing research, the data that has been collected will be analyzed using multiple regression, with the help of SPSS (Statistic Package for Social Science). The results of this study indicate that leadership style has a positive influence on the performance of SMEs, and business practices that run also has a positive effect on the performance of SMEs.